Modeling and optimizing method for axial flux induction motor of electric vehicles - Mei, Jie (2021)
Axial flux induction motors have attracted attention in electric vehicles due to their advantages over conventional motors, including higher efficiency, compact structure, high utilization of materials, and good ventilation and cooling. This paper provides a fast design method for two-stator-one-rotor axial flux induction motor of electric vehicle applications. The proposed method consisting of an accurate motor analytical model and a design variables optimization method based on genetic algorithm. Unlike traditional design of axial flux induction motor with single objective, multi-objective is considered in this work. Based on the proposed method, the performance of axial flux induction motor can be simulated and optimized in much shorter time compared with finite element analysis in ANSYS Maxwell. The comparison results from ANSYS Maxwell can prove the effectiveness and accuracy of the proposed method, and the performance of the final designed motor can meet all the design requirements.